2015
DOI: 10.1111/phen.12089
|View full text |Cite
|
Sign up to set email alerts
|

Female access and diet affect insemination success, senescence and the cost of reproduction in the male Mexican fruit fly Anastrepha ludens

Abstract: Hypotheses exploring the influence of dietary conditions on the life history trade-off between survival and reproductive success are extensively tested in female insects, but are rarely explored in males. Here, the impact of dietary quality and female access on age-specific reproduction and survival of male Mexican fruit flies, Anastrepha ludens Loew (Diptera: Tephritidae), are examined. There is a clear cost of female access for males with access to dietary protein, measurable as a decrease in life expectancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…One important issue that complicates comparisons among species and studies is that the terms Byoung^and Bold^do not always mean the same ages. While in some cases the age differences are only a few days, in other cases flies are tested from emergence to senescence (Papanastasiou et al 2011;Benelli et al 2013;Harwood et al 2015). On the other hand, time of sexual maturation differ among species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One important issue that complicates comparisons among species and studies is that the terms Byoung^and Bold^do not always mean the same ages. While in some cases the age differences are only a few days, in other cases flies are tested from emergence to senescence (Papanastasiou et al 2011;Benelli et al 2013;Harwood et al 2015). On the other hand, time of sexual maturation differ among species.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, time of sexual maturation differ among species. In A. ludens male reproduction (at 23 ± 3°C) has been described in three phases: i) reproductive onset, from 0 to 20 days, ii) reproductive maturity between 25-30 days old (where the highest levels of insemination success are reached), and iii) reproductive senescence, after 30 days when insemination success begins to decline (Harwood et al 2015). Here, we were interested in testing males and females that were already reproductively mature, and comparing them to older senescent males and females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, dietary proteins are detrimental to lifespan (Fanson, Fanson, & Taylor, 2012), but unlike males, females require higher P:C ratios to maximize reproductive effort (e.g., egg production; Le Couteur et al., 2016). Thus, the trade‐off between lifespan and reproduction seems to be more important in females than in males, although there are data showing that this trade‐off also occurs in male Mexican fruit flies Anastrepha ludens , and is related to dietary protein (Harwood et al., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…In wild males, a previous study found older sexually experienced males (36 d old) to have increased mating success compared to 18‐d‐old males, although no benefits in terms of fecundity or fertility for their mates were found (Pérez‐Staples et al ., ). Insemination success is affected by male age, young males from 0 to 20 d old are in reproductive onset, then reproductive maturity (where males reached the highest reproductive success) is reached between 25 and 30 d, and finally senescence begins at 30 d, when insemination success begins to decrease (Harwood et al ., ). However, there is not a clear atrophy of reproductive organ size at these ages, and even at 57 d of age males have more sperm in their seminal vesicles than younger 9‐d‐old males (Reyes‐Hernández & Pérez‐Staples, ).…”
Section: Introductionmentioning
confidence: 99%